A super-high energy density asymmetric supercapacitor based on 3D core–shell structured NiCo-layered double hydroxide@carbon nanotube and activated polyaniline-derived carbon electrodes with commercial level mass loading1. Issue 25 (7th July 2015) - Li, Xiaocheng; Shen, Juanjuan; Sun, Wei; Hong, Xuda; Wang, Rutao; Zhao, Xinhong; Yan, Xingbin
<x xml:space="preserve">Abstract</x> An asymmetric supercapacitor device with an energy density of 89.7 W h kg−1 at commercial level mass loading was successfully fabricated.